Reprise on Commodity Systems Methodology - H. Friedland, William (The International Journal of Sociology of Agriculture and Food, 2021)
Set out over a decade ago, a methodology of commodity systems analysis described five basic foci of research: production practices, grower organization and organizations, labor, science production and application, and marketing and distribution networks. Recent empirical research on several commodity systems in California and on the globalization of fresh fruits and vegetables has indicated the need for an elaboration of the original methodology. A review is made of existing literature relevant to commodity studies and commodity systems analyses as well as assessing several related systems of provision and actor network theory as potential contributors to commodity and commodity systems analysis. Three additional research foci are proposed: scale, sectoral organization and the relationship of the state to the commodity, and commodity culture. Scale refers both to the spatial character of the commodity and the forms of social interaction of actors within the commodity system and also includes the character of the community or communities – spatial and functional – that are part of the commodity system. Sectoral organization deals with whether and how the commodity is organized in or around the competitive, monopoly, or state sectors and how the commodity is regulated or the degree to which the state regulates, intervenes, or supports commodity development. Commodity culture refers to cultural forms found either among commodity producers or consumers, a variable phenomenon with strong cultural elements found in some commodities and absent in others. Empirical cases explore the utility of these augmenting research foci.